A cross-cultural, cross-age, and cross-gender study of Hong Kong and UK secondary students' decision making about a biological conservation issue - Lee, Yeung Chung; Grace, Marcus; Rietdijk, Willeke; Lui, Yuet Chu (International Journal of Science Education, 2019)
The possible roles of culture, gender, and age-related factors in decision making about socioscientific issues (SSIs) have been underexplored. To study the impact of culture and cross-cultural understanding on students’ decision-making, and how these impacts are possibly mediated by age and gender-related variables, 106 11–13 year old students and 60 15–17 year old students from three Hong Kong schools and four UK schools were engaged in decision-making about shark fishing. Data were collected on how students make decisions before and after interacting with their own peers and considering the views of their international counterparts, using discussion records, supplemented with focus group interviews. The findings show that students associated with the culture of shark eating do not necessarily identify with shark fishing. Three dimensions characterise students’ decisions: the human activities to be controlled, the ways to address issues arising from shark fishing, and the concerns underlying students’ decisions. Although students showed support for conserving sharks, there were nuanced differences between the two cultural groups, which were possibly mediated by gender and age factors. The findings provide support to the impact of cultural exchange on their own and others’ views on broadening students’ perspectives and stimulating their critical reasoning.
Keywords: Biology education; comparative study; context-based learning